Evaluation of Seawater Intrusion and Impact on Infrastructure in the Coastal Area of ​​North Surabaya - Soebagio; Kathulistiani, Utari; Pahing, Johan; Datom, Konstantinus (UKaRsT, 2025)
Several wells of coastal residents at North Surabaya experienced changes in odor, taste, and color indicating seawater intrusion. This phenomenon can cause an increase in groundwater salinity, which impacts clean water quality, public health, and infrastructure resilience. Therefore, it is important to evaluate seawater intrusion in the area. This study aims to evaluate the level of seawater intrusion, determine the distribution pattern of intrusion, and identify high-risk zones for seawater intrusion and the level of infrastructure vulnerability to corrosion. The methods used include analysis of physical and chemical parameters of groundwater, intrusion assessment using the Revelle Index and Electrical Conductivity (EC), and mapping based on Geographic Information System (GIS) to determine the distribution pattern of intrusion. The laboratory's well water sample testing showed an average EC score approaching 1500 μS/cm, and the R-value was far above 1. It meant that well water in North Surabaya has been facing seawater intrusion from medium to high levels. It also predicted the distance of seawater intrusion is about 2,5 km from the coastline and has the most significant risk of infrastructure degradation due to corrosion. Seawater intrusion in Surabaya is caused by geographical proximity to the sea, aquifers' hydrodynamic factors, and high groundwater exploitation. The results of this study contribute to providing a seawater intrusion risk map that can be a reference for the government and policymakers in developing mitigation strategies and groundwater management policies to reduce the impact of seawater intrusion.